Retroperitoneal Gas Gangrene Complicating Elective Inguinal Hernia Repair. Issue 3 (1st October 2001) - Privitera, A; Edwards, D P; Cunningham, C
Abstract : Gas gangrene is a well recognised complication of contaminated military wounds. A case of Clostridial myonecrosis following elective inguinal hernia repair is described. The pathology, clinical features and management of this life-threatening condition are reviewed.